ANALYSIS OF A DIFFERENCE IN THE BIOMECHANICAL CHARACTERISTICS ACCORDING TO THE HABITUATION BY HEIGHTS OF SHOES: HIGH-HEEL AND LOW-HEEL SHOES - Cha, Yu (LIFE: International Journal of Health and Life-Sciences, 2020)
This study was performed to comprehensively investigate whether there is a difference in the biomechanical characteristics according to the habituation by heights of shoes of those who habituate to high heeled shoes and low heeled shoes. The women with low heeled habituation show significantly higher values of peak pressures in the lateral forefoot and midfoot areas, and wider contact areas in toes and midfoot than the women with high heeled habituation for the contact area. From the EMG comparison, the women with high heeled habituation show significantly higher maximum peak EMG in GM, and from the percentage of maximum voluntary isometric contraction (%MVIC), the women with high heeled habituation show significantly higher values of the plantarflexion in GM the low heeled shoe user. For the static balance, the women with high heeled habituation show significantly greater values with eyes open. The study was able to verify that there is a significant difference in biomechanical fitness such as foot pressure, %MVIC, etc. Based on the result, this study can be utilized as base data to develop a customized insole that disperses pressure and softens shock absorption of the high heeled shoes.